Unexpected Base-Promoted Synthesis of Tetrasubstituted Furans via Palladium-Catalyzed Oxidation and Cyclization of Carbon–Carbon Triple Bond with Molecular Oxygen - Wang, Lianyue; Li, Jun; Lv, Ying; Zhao, Gongda; Gao, Shuang (Synlett, 2012)
A new approach to the synthesis of tetrasubstituted furans using aromatic alkynes catalyzed by PdCl2 in DMA (N,N-dimethylacetamide)–H2O with dioxygen as the sole oxidant is described, in which the oxygen atom of the furan was from water. The preliminary mechanistic understanding of this transformation was investigated.
Keywords: palladium; oxidation; furans; alkynes; molecular oxygen